Perceptions of Public Management and Educational Improvement in Yala, Thailand: A Community-Based Qualitative Inquiry - Varayut Pukaew; Hendri Koeswara; Ria Aryani (International Journal Labs, 2025)
The education system in Yala, a conflict-sensitive and multicultural province in Southern Thailand, faces persistent challenges shaped by sociopolitical instability, cultural diversity, and governance constraints. This study investigates the perceptions of teachers, community leaders, and local officials regarding public management practices and their influence on educational improvement in Yala. Using a qualitative approach grounded in Community-Based Participatory Research (CBPR), data were collected through nine semi-structured individual interviews and two focus group discussions (FGDs), each involving three participants. Thematic analysis revealed four major insights: (1) a persistent disconnect between national education policies and local realities; (2) uneven access to teacher professional development due to geographic, cultural, and security barriers; (3) the underutilized potential of religious and cultural institutions in education governance; and (4) a trust gap between the community and central authorities that undermines participatory governance. These findings underscore the need for culturally inclusive, decentralized, and conflict-sensitive public management strategies. The study contributes both theoretically and practically by offering locally grounded insights for policymakers, educators, and scholars seeking to improve education systems in post-conflict, multicultural settings.